Liberalizaç\~ao das importaç\~oes: Unilateral ou por meio de acordos comerciais? - Marcelo José Braga Nonnenberg; Fernando José da S. P. Ribeiro; Honorio Kume; Gerlane Gonçalves de Andrade; Helena Nobre de Oliveira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– The literature has been showing that current import tariffs on industrialized products in Brazil are excessively high when compared to countries with similar income per capita. But there's a controversy over the best path to reduce the level of protection, whether through an unilateral tariff reduction or through the negotiation of trade agreements with relevant countries. The aim of this paper is to subsidize this debate, what is made in three ways. First, by analyzing the theoretical matters related to the question; second, by evalutating the internacional experience, what is made through organizing information from different databases concerning trade agreements signed by a huge number of countries in the last decades; and third, through brief case studies of eight middle income countries, whose experience can be used as reference to the Brazilian case: China, Thailand, Russia, Hungary, Poland, Romenia, Mexico and Chile. The paper concludes that high import tariffs doesn't seem to be a precondition for the negotiation and signing of trade agreements and that unilateral tariff reductions and reductions via trade agreements are complementary strategies aimed to satisfy distinct objectives. Therefore, if the country in fact wants to reduce the levels of tariff protection having in sight the economic efficiency and productivity gains that the theoretical literature predicts - and the empirical literature confirms -, the natural way is to make an unilateral liberalization, with the trade agreements playing a complementary role to reach more diversified objectives, not only the economic ones but also geopolitical ones.
Keywords: F10; F15; 330; trade; import tariffs; trade agreements